2020
DOI: 10.1016/j.jenvman.2020.110250
|View full text |Cite
|
Sign up to set email alerts
|

Carbon inequality and economic development across the Belt and Road regions

Abstract: Given the aim of maintaining global warming below 2°C, carbon emission reduction has become a global top priority. Since the Belt and Road Initiative has increasing influence on manufacturing-oriented developing countries, more attention should be paid to carbon emission reduction in these regions. This study conducts a comprehensive analysis by analyzing the carbon inequality and regional development and compares the carbon emissions driven by final demand among countries in and outside the Belt and Road area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Meanwhile, the problem of carbon emission inequality in the Belt and Road Initiative has been studied by some scholars. Han et al ( 2020 ) analyzed the inequality of carbon emissions in the Belt and Road Initiative and found that the level of carbon emission inequality in the Belt and Road Initiative is lower than the direct average. Han et al ( 2020 ) analyzed the data and believed that the level of carbon emission inequality in countries along the Belt and Road Initiative is lower than the world average.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the problem of carbon emission inequality in the Belt and Road Initiative has been studied by some scholars. Han et al ( 2020 ) analyzed the inequality of carbon emissions in the Belt and Road Initiative and found that the level of carbon emission inequality in the Belt and Road Initiative is lower than the direct average. Han et al ( 2020 ) analyzed the data and believed that the level of carbon emission inequality in countries along the Belt and Road Initiative is lower than the world average.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Han et al ( 2020 ) analyzed the inequality of carbon emissions in the Belt and Road Initiative and found that the level of carbon emission inequality in the Belt and Road Initiative is lower than the direct average. Han et al ( 2020 ) analyzed the data and believed that the level of carbon emission inequality in countries along the Belt and Road Initiative is lower than the world average. The above research shows that there is no problem of carbon emission inequality in the Belt and Road Initiative and China and countries along the route can achieve mutual benefit and win-win through the Belt and Road Initiative and jointly carry out carbon emission reduction work.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the aforementioned principles as well as existing literature and data collection [29][30][31], this study establishes the evaluation index system of PV industry along the Belt and Road from five aspects, namely economy, politics, society, ecological environment and resources, as listed in Table 1.…”
Section: Index Selectionmentioning
confidence: 99%
“…For instance, it has been argued that China may reallocate its domestic pollution and overcapacity through the BRI [24] and is playing the leading role in driving carbon footprints within this area [25]. The carbon inequality and economic development of the countries within and outside BRI were compared as well, but without investigating the driving forces for emission growth and the impact of technological differences on responsibility allocation among those nations [26].…”
Section: Introductionmentioning
confidence: 99%